THE METHODOLOGICAL STRUCTURE FOR LEGAL RESEARCH: A PERSPECTIVE FROM THE MALAYSIAN LAND LAW AND ISLAMIC LAW - Ghazali, Noor Azimah; Sipan, Ibrahim; Abas, Farah Nadia; Che Yaacob, Ahmad (PLANNING MALAYSIA, 2021)
A legal research shall be secured with the idea to facilitate a future change; either in the law itself or in the manner of its administration from the production of ‘pure’ academic knowledge which is concerned legal doctrines. Therefore, this paper purpose is to propose a methodological structure for legal research within perspective Malaysian Land Law and Islamic Law to establish a regulation or amendment in the existing foundation. This paper adopts method of content analysis to understanding on the underlying reasons through expert opinions on the legal issues. The finding of this research revealed that a legal methodological framework is easily simplified in form of system theory approach. This type of methodological structure is common amongst the legal researchers, lawyers and legal scholars who embrace Pure and Applied Legal Research. The methodological structure for legal research in form of system theory shall make a better regulation proposal in the perspective of Malaysian Land Law and Islamic Law. By adopt this methodological structure; researchers shall propose new regulation or amendments as legal researchers, lawyers and legal scholars.